Study of incidence of premature ovarian failure in patient attending outpatient department for infertility in a tertiary care centre - Amber, Qazi Jaweria; Palve, Tushar Tatyaba (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: To assess the incidence of premature ovarian failure in cases attending infertility outpatient Department of Obstetrics and Gynecology in a tertiary care centre. A total of 350 patients attending infertility opd were screened over period of 150 days from which authors observed premature menopause in 10 cases accounting for an incidence of 2.8%. POF affects approximately one in 10,000 women by age 20; one in 1,000 women by age 30; one in 100 women by age 40. Premature ovarian failure is a common cause of infertility in women. Methods: Patient attending outpatient Department of Obstetrics and Gynecology with age less than 40 years and infertility, symptoms of menopause were enrolled for the study for duration of 150 days. Results: Present study authors found a total of 2.8% of patient presenting in our outpatient department for infertility had Premature ovarian failure.80% of them were symptomatic suffering with symptoms of hormonal deficiencies .100% of patient with infertility diagnosed as premature ovarian failure had low AMH and High FSH and LH levels indicating poor prognosis. Conclusions: Patient presenting with infertility and amenorrhoea can be cases of premature menopause. Here it is essential to investigate and treat the patient. Infertility might be one of the early presenting symptoms if not the first one. These patients if treated and diagnosed early can have a better living. Considering the wide spectrum of functional derangements in patient with early menopause and benefits of early hormone replacements these patients should be diagnosed and treated early.